Look around you--nature as an educator - Cain, Emma M. (My University, 1902)
Introduction: What a world of knowledge we may gain upon looking around us. Many of the grand old elms are still standing which for centuries have spread their branches above our heads. Did you ever stop to listen to the murmur of the stream as it flows majestically in its bed and ever wonder how or why it came to be there? Again, as you go into the meadows on a bright May morning when the dew is sparkling on the grass and flowers; the birds are singing among the branches of the trees and the fresh morning breezes cool your brow as well as the songs from nature lighten your heart and refresh your mind, have you ever meditated for one moment upon the history of this beautiful world and above all its creator?
Citation: Cain, Emma M. Look around you--nature as an educator. Senior thesis, Kansas State Agricultural College, 1902.
Morse Department of Special Collections
Keywords: Nature; Education; Theses; Manuscripts (documents)